Sauna in patients with hypertension - Pawlicki, Mateusz Maciej; Pawlicki, Bartłomiej; Łopuszyńska, Anna Małgorzata; Misztal, Zofia; Kozioł, Magdalena; Lorenc, Karol (Journal of Education, Health and Sport, 2019)
Saunas are very popular around the world, especially in some specific regions like Finland. Sitting in a temperature of 45-110°C with intervals often including cold baths influence our bodies in different aspects. Apart from being an addition to asthma or depression treatment, it works well as prevention of heart diseases and hypertension. Sauna is also believed to be able to reduce increased blood pressure values. Because of its safety it can be easily prescribed for all patients without few contraindications.